2019
DOI: 10.1155/2019/7213913
|View full text |Cite
|
Sign up to set email alerts
|

Diosgenin and Its Fenugreek Based Biological Matrix Affect Insulin Resistance and Anabolic Hormones in a Rat Based Insulin Resistance Model

Abstract: Fenugreek is known since ancient times as a traditional herbal medicine of its multiple beneficial effects. Fenugreek’s most studied and employed effect is its hypoglycemic property, but it can also be useful for the treatment of certain thyroid disorders or for the treatment of anorexia. The regulation of glucose homeostasis is a complex mechanism, dependent on the interaction of different types of hormones and neurotransmitters or other compounds. For the study of how diosgenin and fenugreek seeds modify ins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 77 publications
0
13
0
1
Order By: Relevance
“…From the results of direct measurements before and during the HEGC protocol-i.e., body weight (BW), fasting plasma glucose (FPG), fasting plasma insulin (FPI), rate of glucose infusion (GI), rate of insulin infusion (II), steady state plasma glucose (SSPG), steady state plasma insulin (SSPI)-different indices were calculated [66], the formulas of which are as follows: GIR = glucose infusion rate (not to be mistaken with the rate of the glucose infusion (GI)) GIR = GI (uL/min) BW (g) * 220…”
Section: Calculated Indicesmentioning
confidence: 99%
“…From the results of direct measurements before and during the HEGC protocol-i.e., body weight (BW), fasting plasma glucose (FPG), fasting plasma insulin (FPI), rate of glucose infusion (GI), rate of insulin infusion (II), steady state plasma glucose (SSPG), steady state plasma insulin (SSPI)-different indices were calculated [66], the formulas of which are as follows: GIR = glucose infusion rate (not to be mistaken with the rate of the glucose infusion (GI)) GIR = GI (uL/min) BW (g) * 220…”
Section: Calculated Indicesmentioning
confidence: 99%
“…Diosgenin is a steroidal sapogenin that could be found as a major bioactive compound in tubers of wild Yam plants ( Dioscorea villosa ) and several other plants including Costus , Smilax , Dioscorea , and Trigonella [ 10 , 11 ]. Diosgenin has multiple pharmaceutical advantages including anti-inflammatory [ 12 ], hepatoprotective [ 13 ], anti-hypercholesterolemic [ 14 , 15 ], anti-osteoporotic [ 16 ], prevents spinal cord injury [ 17 ], prevents testicular damage in diabetic rats [ 18 ], attenuates Parkinson’s disease [ 19 ], and modulates insulin resistance and anabolic hormones [ 20 ]. The anti-hypercholesterolemic studies have reported that diosgenin is safe for consumption and has significant inhibition toward gastrointestinal uptake of dietary cholesterol and also the regulation of bile acids [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Decreased activity of GSH and CAT in the level in the DEN control group was observed. Diosgenin treated group increased the GSH and CAT levels, which suggest its antioxidant and hepatoprotective property of diosgenin 21 .…”
Section: Fig 2: Effect Of Diosgenin In Den Induced Hepatotoxicity Onmentioning
confidence: 77%